Ochronotic arthropathy: skeletal manifestations and orthopaedic treatment - Khaled Hamed Salem; Alyaa Diaa Elmoghazy (EFORT Open Reviews, 2025)
Alkaptonuria is an extremely rare disorder of tyrosine metabolism caused by an autosomal recessive enzymatic deficiency of homogentisic acid (HGA) oxidase, causing its accumulation in collagenous structures, especially in hyaline cartilage. It is characterized by a triad of homogentisic aciduria, bluish-black discoloration of connective tissues (ochronosis) and arthropathy of the spine and large weight-bearing joints. Several clinical manifestations were described including coronary and valvular calcification, aortic stenosis, limited chest expansion, and renal, urethral and prostate calculi as well as ocular and cutaneous pigmentation. Skeletal affection usually presents as spondylotic changes of the spine. The knee is the most common peripheral joint to be involved. Enthesopathy or tendon ruptures may occur, and reduced bone density is not unusual. A low-protein diet and ascorbic acid may reduce HGA levels. Nitisinone can safely and effectively reduce HGA production and urinary excretion. In severe ochronotic arthropathy, joint arthroplasty can offer reliable pain relief and excellent functional outcomes. Cementless fixation is successful in young patients.